Effect of stress factors associated with postharvest citrus conditions on the viability and biocontrol activity of Clavispora lusitaniae strain 146 - Pereyra, Martina María; Díaz, Mariana Andrea; Meinhardt, Friedhelm; Dib, Julián Rafael (PloS one, 2020)
Only quite recently, we have shown that yeast strains Clavispora lusitaniae 146 and Pichia fermentans 27 can act as efficient biocontrol agents for combating postharvest fungal diseases in lemons. During postharvest and storage conditions, microorganisms are subject to different stress factors that could affect both their survival and their protective capacity. Understanding the tolerance of yeasts to environmental stress factors could support the future development and commercial application of biological control formulations based on such organisms. Thus, the impact of different stressors on the viability and protection efficiency of C. lusitaniae strain 146 and P. fermentans strain 27 was evaluated, and the yeasts were subjected to oxidative stress, thermal treatments, exposure to NaOCl, osmotic stress, and ultraviolet irradiation. Candida oleophila strain O served as the reference control. C. lusitaniae 146 was more resistant to H.sub.2 O.sub.2 in plate assays; however, in liquid media there was no significant difference to the other strains. Strain 146 was less affected by NaOCl, being able to survive with 300 ppm. P. fermentans 27 was the strain most heavily affected by osmotic pressure, while strains 146 and strain O showed a similar adaptation. UV-B irradiation severely affected C. oleophila and P. fermentans, while C. lusitaniae was the most resistant. Strains 146 and 27 were similarly tolerant to thermal shocks, compared to the reference strain, which was less viable. In in vivo tests, exposure to 10 mM H.sub.2 O.sub.2, 45°C or 200 ppm NaOCl prior to fruit inoculation, reduced the antagonistic activity against the pathogen Penicillium digitatum. However, in no case was the biocontrol efficiency reduced to less than 50%. As C. lusitaniae 146 demonstrated a great potential to combat P. digitatum under a wide range of conditions, the organism is a promising candidate as an effective and valuable alternative to toxic fungicides.